Revolutionizing cancer treatment: the power of bi- and tri-specific T-cell engagers in oncolytic virotherapy - Zarezadeh Mehrabadi, Ali; Tat, Mahdi; Ghorbani Alvanegh, Akbar; Roozbahani, Fatemeh; Esmaeili Gouvarchin Ghaleh, Hadi (Frontiers in Immunology, 2024)
Bi-or tri-specific T cell engagers (BiTE or TriTE) are recombinant bispecific proteins designed to stimulate T-cell immunity directly, bypassing antigen presentation by antigen-presenting cells (APCs). However, these molecules suffer from limitations such as short biological half-life and poor residence time in the tumor microenvironment (TME). Fortunately, these challenges can be overcome when combined with OVs. Various strategies have been developed, such as encoding secretory BiTEs within OV vectors, resulting in improved targeting and activation of T cells, secretion of key cytokines, and bystander killing of tumor cells. Additionally, oncolytic viruses armed with BiTEs have shown promising outcomes in enhancing major histocompatibility complex I antigen (MHC-I) presentation, T-cell proliferation, activation, and cytotoxicity against tumor cells. These combined approaches address tumor heterogeneity, drug delivery, and T-cell infiltration, offering a comprehensive and effective solution. This review article aims to provide a comprehensive overview of Bi-or TriTEs and OVs as promising therapeutic approaches in the field of cancer treatment. We summarize the cutting-edge advancements in oncolytic virotherapy immune-related genetic engineering, focusing on the innovative combination of BiTE or TriTE with OVs.